Characteristics and motives of non-responders in a stepwise cardiometabolic disease prevention program in primary care. (10th May 2021) - Badenbroek, Ilse F; Nielen, Markus M J; Hollander, Monika; Stol, Daphne M; de Wit, Niek J; Schellevis, François G
Abstract: Background: A high response rate is an important condition for effective prevention programs. We aimed at gaining insight into the characteristics and motives of non-responders in different stages of a stepwise prevention program for cardiometabolic diseases (CMD) in primary care. Methods: We performed a non-response analysis within a randomized controlled trial assessing the effectiveness of a stepwise CMD prevention program in the Netherlands. Patients between 45 and 70 years without known CMD were invited for stage 1 of the program, completing a CMD risk score. Patients with an increased risk were advised to visit their general practice for additional measurements, stage 2 of the program. We analyzed determinants of non-response using data from the risk score, electronic medical records, questionnaires and Statistics Netherlands. Results: Non-response in stage 1 was associated with a younger age, male sex, a migration background, a low prosperity score, self-employment, being single and having lower consultations rates in general practice. Non-response in stage 2 was associated with a low prosperity score, being employed, having no chronic illness, smoking, a normal waist circumference, a negative family history for cardiovascular disease or diabetes and having a lower consultation rate. More than half of the non-responders in stage 2 reported not visiting the GP because they did not expect to have any CMD, despite their increased risk. Conclusions: To achieve a larger and more equal uptake of prevention programs for CMD, we should use methods adapted to characteristics of non-responders, such as targeted invitation methods and improved risk communication.